Comparative efficacy of Nice knot versus lag screw in augmenting locking plate fixation for comminuted clavicular fractures: a retrospective cohort study - Huaxian Huang; Chaoran Hu; Yongfei Cao; Qin Luo; Chaode Cen; Honghao Yuan; Yungui Li; Aixin Cao (BMC Musculoskeletal Disorders)
Abstract Background This study aims to systematically evaluate and compare the intraoperative outcomes, postoperative efficacy, and clinical prognosis of Nice knot versus lag screw in augmenting locking plate fixation for comminuted clavicular fractures. Through comprehensive assessment of different therapeutic approaches, we endeavor to provide more scientific and effective therapeutic options for patients with comminuted clavicular fractures. Methods From January 2020 to December 2022, 123 patients with unilateral midshaft comminuted clavicular fractures were enrolled, including 58 cases in the Nice knot (NK) group and 65 cases in the lag screw (LS) group. The general information, intraoperative conditions, postoperative clinical outcomes, and imaging results of patients in both groups were recorded and compared. The Visual Analog Scale (VAS) score, Constant-Murley score, Disabilities of the Arm, Shoulder and Hand (DASH) score and incidence of complications were assessed between the two groups. Results There were no significant differences in general information between the two groups. The NK group demonstrated significantly shorter operation time and less intraoperative blood loss compared to the LS group (P < 0.01). Both groups had one case of implant failure, while two cases of nonunion were observed in the LS group (P > 0.05). Follow-up results revealed no significant differences in VAS score, QuickDASH score, or Constant-Murley score between the two groups (P > 0.05). Conclusion This study demonstrated that both the Nice knot and lag screw achieved favorable clinical outcomes in augmenting locking plate fixation for Robinson IIB clavicle fractures. However, the NK group exhibited advantages of decreased intraoperative blood loss and shorter operation time, which makes it a valuable, effective, and safe surgical approach for managing Robinson IIB clavicle fractures, worthy of clinical promotion.